\(2n+3⋮3n+4\Leftrightarrow6n+9⋮3n+4\)
\(\Leftrightarrow2\left(3n+4\right)+1⋮3n+4\Leftrightarrow1⋮3n+4\)
\(\Rightarrow3n+4\inƯ\left(1\right)=\left\{\pm1\right\}\)
3n + 4 | 1 | -1 |
3n | -3 | -5 |
n | 1 | -5/3 |
\(2n+3⋮3n+4\)
Ta có: \(2n+3=3\left(2n+3\right)=6n+9\)
\(3n+4⋮3n+4\Leftrightarrow2\left(3n+4\right)⋮3n+4\Leftrightarrow6n+8⋮3n+4\Leftrightarrow\left(6n+9\right)-\left(6n+8\right)⋮3n+4\)
\(\Leftrightarrow1⋮3n+4\Leftrightarrow3n+4\inƯ\left(1\right)=\left\{\pm1\right\}\)
\(\Leftrightarrow n\in\left\{-1;\frac{-5}{3}\right\}\)